1990
DOI: 10.1128/aac.34.6.1014
|View full text |Cite
|
Sign up to set email alerts
|

Comparative efficacies of ciprofloxacin, pefloxacin, and vancomycin in combination with rifampin in a rat model of methicillin-resistant Staphylococcus aureus chronic osteomyelitis

Abstract: The efficacies of the quinolones ciprofloxacin and pefloxacin alone and in combination with rifampin were compared with those of vancomycin alone and in combination with rifampin in a rat model of chronic osteomyelitis caused by methicillin-resistant Staphylococcus aureus. Neither the quinolones nor vancomycin alone was effective in reducing titers of organisms in bone after therapy, while rifampin alone was effective. All combination regimens with rifampin were more effective than the regimen with rifampin al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
0
1

Year Published

1993
1993
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(46 citation statements)
references
References 15 publications
1
44
0
1
Order By: Relevance
“…Rifampicin is a potent antibiotic that is especially effective against Staphylococcus, which sometimes show resistance to beta-lactam antibiotics (Henry et al, 1987;Dworkin et al, 1990;O'Reilly et al, 1992;Littlewood-Evans et al, 1997;Rissing, 1997;Costerton et al, 1999). Furthermore, rifampicin has been shown to be an effective agent for treating bacteria in biofilms (Widmer et al, 1992), which Costerton et al (1999) reported to be important in the pathogenesis of bone and joint infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rifampicin is a potent antibiotic that is especially effective against Staphylococcus, which sometimes show resistance to beta-lactam antibiotics (Henry et al, 1987;Dworkin et al, 1990;O'Reilly et al, 1992;Littlewood-Evans et al, 1997;Rissing, 1997;Costerton et al, 1999). Furthermore, rifampicin has been shown to be an effective agent for treating bacteria in biofilms (Widmer et al, 1992), which Costerton et al (1999) reported to be important in the pathogenesis of bone and joint infection.…”
Section: Discussionmentioning
confidence: 99%
“…The efficiency of the combination therapy of rifampicin and ciprofloxacin in controlling orthopedic infections has been demonstrated in clinical and experimental studies (Hendry et al, 1987;Dworkin et al, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…They both have excellent oral bioavailability and safety, allowing them to be used for prolonged courses of therapy. The quinolone-rifampin combinations that have been studied include ciprofloxacin, perfloxacin, ofloxacin, levofloxacin, gatifloxacin, and moxifloxacin (18,73,74,106,117,137,279).…”
Section: Staphylococcimentioning
confidence: 99%
“…Although the bactericidal agent rifampin has excellent antistaphylococcal activity, the emergence of rifampin resistance when used as a single agent has limited its use in this manner (19)(20)(21). This development of rifampin resistance in infections that are difficult to treat (endocarditis and osteomyelitis) has been documented in many papers and supports the requirement that rifampin should not be administered as a single agent (2,4,8,9,13). Studies of the combination of rifampin and other antibacterials have reported mixed results, with several studies reporting antagonism or indifference (2,5,17,18).…”
mentioning
confidence: 99%